1976
DOI: 10.1136/adc.51.10.755
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline membrane disease, alkali, and intraventricular haemorrhage.

Abstract: . (1976). Archives of Disease in Childhood, 51, 755. Hyaline membrane disease, alkali, and intraventricular haemorrhage. The relation between intraventricular haemorrhage (IVH) and hyaline membrane disease (HMD) was studied in singletons that came to necropsy at Hammersmith Hospital over the years 1966-73. The incidence of IVH in singleton live births was 3 -22/1000 and of HMD 4-44/1000. Although the high figures were partly due to the large number of low birthweight infants born at this hospital, the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 23 publications
0
16
0
5
Order By: Relevance
“…Assuming a normal CBV in healthy term infants of 2.22 ml/100 g brain [30] , bolus infusion of NaHCO 3 results in a 7% increase in CBV. NaHCO 3 administration has been associated with an increased risk of IVH [3][4][5][6] . Changes in CBV might contribute to the pathogenesis of IVH after NaHCO 3 infusion in preterm infants with vulnerable blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a normal CBV in healthy term infants of 2.22 ml/100 g brain [30] , bolus infusion of NaHCO 3 results in a 7% increase in CBV. NaHCO 3 administration has been associated with an increased risk of IVH [3][4][5][6] . Changes in CBV might contribute to the pathogenesis of IVH after NaHCO 3 infusion in preterm infants with vulnerable blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Biol Neonate 2006;90: [122][123][124][125][126][127] 123 NaHCO 3 administration as a possible risk factor for IVH [3][4][5][6] . NaHCO 3 administration provokes hypercapnia [7][8][9] , hyperosmolarity [7,10,11] and changes in hemodynamics [12][13][14] which can lead to changes in cerebral blood fl ow (CBF) when auto-regulation is impaired.…”
Section: Sodium Bicarbonate In Preterm Infantsmentioning
confidence: 99%
“…Injection of hypertonic solutions for example has been suggested as a possible cause of IVH (Simmons et al, 1974;Wigglesworth et al, 1976). Clearly this possibility may be excluded if it is found that administration of alkali occurs predominantly after IVH in an attempt to reverse the resulting acidosis (Roberton and Howat, 1975;Anderson et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…В 70-е годы и начале 80-х годов прошлого века произошел прорыв в области изучения этиопа-тогенеза развития и диагностики ВЖК у новорожден-ных. В связи с бурным внедрением в медицинскую практику метода УЗИ головного мозга многие уче-ные заинтересовались вопросами диагностирования [18,33,41,42], характера и патогенеза вну-тримозговых кровоизлияний, в том числе ВЖК [15,16,21,26,27], а также разрабатывали методы их диаг-ностики [17,34]. Так, W. Szymonowicz и соавт.…”
Section: Introductionunclassified